Teaching undergraduate medical students virtual consultation skills: a mixed-methods interventional before-and-after study - Edie Booth; Kate McFetridge; Evelyn Ferguson; Catherine Paton (BMJ Open)
Objectives To evaluate the impact and transferability of a novel teaching method on virtual communication skills for final year medical students.Design Mixed-methods, interventional before-and-after study.Setting NHS Lanarkshire, Scotland.Participants 21 final year medical students on their obstetrics and gynaecology (O&G) placement from September to December 2020.Interventions A two-part teaching session on virtual communication skills.Main outcome measures Self-reported confidence in conducting consultations preteaching and post-teaching, exposure to virtual consultations, usefulness of teaching and transferability to primary care. Data were collected using preteaching and post-teaching evaluation tools and an online survey.Results Of 21 participants, 1 student did not attend the second session so was excluded from post-teaching evaluation results and the online survey. Preteaching results were collected from 21 participants and post-teaching results from 20. Mean confidence scores increased across all domains post-teaching. Mean confidence in opening the consultation increased from 2.67 (95% CI 2.21 to 3.13) to 4.70 (95% CI 4.50 to 4.90); history-taking from 3.38 (95% CI 3.07 to 3.69) to 4.45 (95% CI 4.19 to 4.71); decision-making and forming a management plan from 2.62 (95% CI 2.28 to 2.96) to 3.90 (95% CI 3.66 to 4.14) and closing the consultation from 2.81 (95% CI 2.45 to 3.17) to 4.60 (95% CI 4.38 to 4.81). There was no change in exposure to virtual consultations during O&G placement. 16 (80%) participants responded to the online survey; 14 (87.5%) rated the sessions ‘very useful’ and all 16 considered them worthwhile continuing. 12 (75%) had the opportunity to practise virtual consultations on general practitioner, mostly via telephone.Conclusions We found that teaching students virtual consultation skills improved short term confidence and were transferable to primary care placements. Future research is suggested to assess this teaching model following adaptation and incorporation into medical education and training across specialties and grades. It would be useful to evaluate the impact on competence post intervention through observed skills.